2021
DOI: 10.3390/foods10071652
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Selected Phenolic Compounds against Planktonic and Biofilm Cells of Food-Contaminating Yeasts

Abstract: Phenolic compounds are natural substances that can be obtained from plants. Many of them are potent growth inhibitors of foodborne pathogenic microorganisms, however, phenolic activities against spoilage yeasts are rarely studied. In this study, planktonic and biofilm growth, and the adhesion capacity of Pichia anomala, Saccharomyces cerevisiae, Schizosaccharomyces pombe and Debaryomyces hansenii spoilage yeasts were investigated in the presence of hydroxybenzoic acid, hydroxycinnamic acid, stilbene, flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…A similar phenolic profile was detected in sugarcane leaves of different genotypes [ 25 ], in sugarcane molasses extract [ 26 ], and sugarcane bagasse polyphenols extracted with 60% ( v : v ) ethanol assisted by ultrasound [ 27 ]. In all studies, the diversity of compounds identified was slightly different from those identified in this study; however, the groups of identified compounds were the same.…”
Section: Resultsmentioning
confidence: 67%
“…A similar phenolic profile was detected in sugarcane leaves of different genotypes [ 25 ], in sugarcane molasses extract [ 26 ], and sugarcane bagasse polyphenols extracted with 60% ( v : v ) ethanol assisted by ultrasound [ 27 ]. In all studies, the diversity of compounds identified was slightly different from those identified in this study; however, the groups of identified compounds were the same.…”
Section: Resultsmentioning
confidence: 67%
“…The extract in general and more specifically its phenolic constituents could have altered the hydrophobicity of the cell membrane, making it more hydrophilic and causing detachment from the host cell [ 101 , 102 ]. Besides, the functional group attached to the phenyl ring plays a crucial role in inhibiting the yeast–cell interaction [ 103 ]. Raut et al reported that phenylpropanoids of plant origin, chemical compounds isolated also from O. crenata [ 36 ], are able to prevent the growth, adhesion, yeast-to-hypha transition, and biofilm formation of C. albicans [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two phenolic compounds used in the study, i.e., vanillin and cinnamic acid, and the synthetic compounds, i.e., sodium benzoate, potassium sorbate, and sodium diacetate, were purchased from Sigma-Aldrich (Munich, Germany). The phenolic compounds were selected based on a previous investigation that indicated very high antimicrobial activity of the two natural compounds against food spoilage yeasts [ 27 ]. The stock solutions of the phenolics and synthetic compounds were prepared in 10% ( v/v ) ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…The MICs of vanillin and cinnamic acid against planktonic growth of the tested yeasts were reconfirmed using the microdilution technique described previously [ 27 ]. The MIC values of the synthetic preservatives on planktonic yeasts were assayed through a microplate method previously described by Zambrano et al [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation